Impacts of supermarkets on farm household nutrition in Kenya - Christine G. K. Chege; Camilla I. M. Andersson; Matin Qaim (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2014)
Many developing countries are experiencing a food system transformation with a rapid growth of supermarkets. Research has shown that smallholder farmers can benefit from supplying supermarkets in terms of higher productivity and income. Here, we analyze impacts on farm household nutrition. Building on data from vegetable farmers in Kenya, we show that participation in supermarket channels has sizeable positive effects: calorie, vitamin A, iron, and zinc consumption are all increased by 15% or more. We also analyze impact pathways, using simultaneous equation models. Supermarket-supplying households have higher incomes, a higher share of land under vegetables, and a higher likelihood of male control of revenues. Furthermore, income and the share of land under vegetables have positive impacts, while male control of revenues has negative impacts on dietary quality. The total nutrition effects of supermarket participation could be even more positive if women were able to keep their control over farm revenues in the process of commercialization. The methods developed and used may also be useful for other impact studies to better understand agriculture-nutrition linkages.
Keywords: 330; supermarkets; smallholder farmers; nutrition impact; dietary quality; gender; Kenya